2018
DOI: 10.1021/jacs.7b12430
|View full text |Cite
|
Sign up to set email alerts
|

ATP Site Ligands Determine the Assembly State of the Abelson Kinase Regulatory Core via the Activation Loop Conformation

Abstract: The constituent SH3, SH2, and kinase domains of the Abl kinase regulatory core can adopt an assembled (inactive) or a disassembled (active) conformation. We show that this assembly state strictly correlates with the conformation of the kinase activation loop induced by a total of 14 ATP site ligands, comprising all FDA-approved Bcr-Abl inhibiting drugs. The disassembly of the core by certain (type II) ligands can be explained by an induced push on the kinase N-lobe via A- and P-loop toward the SH3 domain. A si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
70
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(78 citation statements)
references
References 44 publications
6
70
2
Order By: Relevance
“…Conversely, the SH3 domain of Abl-1 V256C/2a complex was efficiently enriched by the immobilized SH3 ligand, consistent with DFG-out stabilizing inhibitor 2a promoting an open, intramolecularly disengaged Abl-1 SH3-SH2-CD module, like its underivatized counterpart. Thus, consistent with previous observations, 25,29 an inhibitor that stabilizes the DFG-out inactive ATP-binding site conformation significantly promotes a regulatory domain-disengaged conformation of Abl-1's SH3-SH2-CD module. Inhibitors that stabilize the helix aC-out inactive ATP-binding site conformation promote a closed Abl-1's SH3-SH2-CD module, which further highlights the Src-like allosteric communication between Abl-1's regulatory domains and its ATP-binding site.…”
Section: Results and Discussion Inhibitors Divergently Modulate The Gsupporting
confidence: 92%
See 3 more Smart Citations
“…Conversely, the SH3 domain of Abl-1 V256C/2a complex was efficiently enriched by the immobilized SH3 ligand, consistent with DFG-out stabilizing inhibitor 2a promoting an open, intramolecularly disengaged Abl-1 SH3-SH2-CD module, like its underivatized counterpart. Thus, consistent with previous observations, 25,29 an inhibitor that stabilizes the DFG-out inactive ATP-binding site conformation significantly promotes a regulatory domain-disengaged conformation of Abl-1's SH3-SH2-CD module. Inhibitors that stabilize the helix aC-out inactive ATP-binding site conformation promote a closed Abl-1's SH3-SH2-CD module, which further highlights the Src-like allosteric communication between Abl-1's regulatory domains and its ATP-binding site.…”
Section: Results and Discussion Inhibitors Divergently Modulate The Gsupporting
confidence: 92%
“…Recent studies have shown that the ability of inhibitors to flip the DFG-motif of Abl-1's activation loop highly correlates with their promotion of an open global conformation of Abl-1's SH3-SH2-CD module. 29 Our observations in Src made us interested in revisiting the molecular binding features of 14 ligands that have previously been reported to promote an open global conformation of Abl-1, which was determined by characteristic NMR 1 H-15 N backbone chemical shifts within the SH3 and SH2 domains ( Figure S4). 29 We found that all inhibitors-including imatinib, nilotinib, ponatinib, rebastinib, and bafetinib-that promote an open global conformation of Abl-1's SH3-SH2-CD module also form a H-bonding interaction with the side-chain of Abl-1's Glu286 that stabilize its helix aC in the active conformation ( Figure S5).…”
Section: Results and Discussion Inhibitors Divergently Modulate The Gmentioning
confidence: 99%
See 2 more Smart Citations
“…Less of an issue perhaps since Class-5 and Class-6 conformations that were obtained from the released ligand-bound structures (Figure 1b), as well as taking conformational flexibility into account, suggests that the EGFR kinase-ligand binding would induce a specific binding mode and EGFR kinase conformation change. Recently, Sonti et al 38 reported a similar ligand-induced binding mechanism for Abelson tyrosine kinase (Abl). Abl belongs to the TK group, like the EGFR kinase, and has 60% sequence similarity 48 .…”
Section: Discussionmentioning
confidence: 97%